MEKANISME BAGI HASIL PADA LEMBAGA KEUANGAN MIKRO SYARIAH (Studi Persepsi Nasabah Tentang Pembiayaan Bagi Hasil) - Muhammad Kamal Zubair (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2011)
This research is intended to find customer understanding on profit sharingconcept on BMT Fauzan Adzimah in Parepare. Customer perception onprofit sharing of the BMT shows higher rank on the level of 67%. This canbe seen in some factors: level of understanding, decision on certain object,emotional engagement and behavior because of emotion and attitude.This can happen because of the people understanding and access towardfinancing system and also the promotion of BMT. The existence of BMTFauzan Adzimah through profit sharing has provide high positive outcomein community vocation in developing micro business in Parepare.